Perlindungan Hukum Terhadap Konsumen Jasa Umroh/Haji Dalam Perbuatan Melawan Hukum - Wahyu Hidayat; Agus Sarono (Notarius, 2022)
Minister of Religion Regulation No. 8 of 2018 concerning the implementation of Umrah worship expeditions has provided a sufficient basis for protection for Umrah pilgrims, including in the form of health protection, life insurance coverage, incidents, or management of congregational documents that have disappeared during the worship expedition. The limited funds that travel operators often feel cause obstacles when providing the protection facilities that have been mentioned, due to the low costs imposed on the congregation by cutting insurance costs. The type of research used in this article is normative juridical research in the case approach, because it will conceptualize law as something that refers to legal norms and principles contained in statutory regulations and court decisions. It is known that there are also umrah organizers who from the beginning did not intend to insure the Umrah congregation. Such a situation, among others, is the absence of routine controls on the organizers of the Umrah trip, through repressive steps, namely the government acts when there is a complaint from the congregation.Keywords: Umrah travel; legal protection; Umrah pilgrims.Abstrak Peraturan Menteri Agama No. 8 Tahun 2018 tentang Penyelenggaraan Ekspedisi Ibadah Umroh telah memberikan landasan proteksi yang cukup bagi Jemaah Umroh, antara lain berupa proteksi kesehatan, jaminan asuransi jiwa, insiden, ataupun pengelolaan dokumen Jemaah yang lenyap sepanjang ekspedisi beribadah. Keterbatasan dana yang kerap dirasakan penyelenggara travel menyebabkan hambatan ketika menyediakan fasilitas perlindungan yang telah disebutkan, disebabkan dari rendahnya biaya yang diberlakukan untuk Jemaah dengan memangkas beban asuransi. Jenis penelitian yang digunakan dalam artikel ini adalah penelitian yuridis normatif dalam pendekatan kasus, karena akan mengkonsepkan hukum sebagai sesuatu yang mengacu kepada norma dan prinsip hukum yang tercantum pada peraturan undang-undang dan putusan pengadilan. Diketahui terdapat pula pelaku usaha umroh yang sejak awal tidak berniat mengasuransikan jemaah umroh. Keadaan seperti itu antara lain dengan tidak terdapatnya pengendalian rutin pada penyelenggara perjalanan umroh, melalui langkah bersifat represif, yaitu pemerintah bertindak apabila ada pengaduan dari Jemaah.Kata Kunci : travel umroh; perlindungan hukum; jemaah umroh.